Clinicopathological Implications of the BRAFV600E Mutation in Papillary Thyroid Carcinoma of Ukrainian Patients Exposed to the Chernobyl Radiation in Childhood: A Study for 30 Years After the Accident - Zurnadzhy, Liudmyla; Bogdanova, Tetiana; Rogounovitch, Tatiana I.; Ito, Masahiro; Tronko, Mykola; Yamashita, Shunichi; Mitsutake, Norisato; Bolgov, Michael; Chernyshov, Serhii; Masiuk, Sergii; Saenko, Vladimir A. (Frontiers in Medicine, 2022)
With time after the Chernobyl accident, the number of papillary thyroid carcinomas (PTCs) driven by the BRAFV600E oncoprotein is growing in patients exposed to radiation at a young age. Clinicopathological associations of BRAFV600E in PTCs from patients with internal radiation history have not been sufficiently studied so far. This work analyzes the structural characteristics, proliferative activity, invasive features, clinical information, and dosimetric data in the BRAFV600E-positive and BRAFV600E-negative PTCs from the Ukrainian patients exposed to Chernobyl radiation and treated over 30 years after the accident. The study included 428 PTCs from patients aged 4–49 years at surgery who lived in the six northern regions of Ukraine most contaminated by 131I, were ≤18 years of age at the time of exposure, and were operated on from 1990 to 2017. Immunohistochemical staining for BRAFV600E was performed with the VE1 antibody. The probability of causation (POC) of a tumor due to radiation was determined using an interactive online NIH/NCI software. BRAFV600E was detected in 136/428 (31.8%) PTCs. In comparison with the BRAFV600E-negative PTCs, the BRAFV600E-positivity was associated with older patient age at the accident and at surgery, a longer period of latency, and lower POC. The BRAFV600E-positive PTCs were characterized by smaller tumor size, higher Ki67 labeling index, more frequent oncocytic changes, multifocality, and dominant papillary growth pattern. Tumor invasive features were less frequent in the BRAFV600E-positive PTCs and did not change with POC level. Despite a less aggressive tumor phenotype, BRAFV600E was a risk factor for recurrence, namely radioiodine-refractory (RAI-R) recurrent metastases. Multivariate models of RAI-R included BRAFV600E and/or histopathological parameters closely correlating with BRAFV600E such as tumor size, multifocality, dominant papillary growth pattern, or oncocytic changes. Thus, the BRAFV600E-positive PTCs from patients from a high-risk group for radiogenic thyroid cancer diagnosed in the 30 years after the Chernobyl accident did not display higher invasiveness regardless of POC level, but in view of the prognostic impact of this genetic alteration, knowledge of the BRAF status may be beneficial for middle-aged patients with radiogenic PTC considered for RAI therapy, and suggests more careful follow-up of patients with the BRAFV600E-positive tumors.